The sagittal soft tissue changes relating to the surgical correction of maxillary deficient class III malocclusions. - Dancaster, J.T. (My University, 2014)
This study assessed the sagittal soft tissue changes in relation to hard tissue changes as seen on lateral cephalometric radiographs of twenty six Class III patients who had undergone maxillary advancement surgery. Thirteen of the patients had in addition received mandibular surgery. Radiographs were available at the immediate pre-surgical and at various post-sv,rgical stages ranging between 3 months and 16 months. Twenty six cephalometric landmarks were identified and six linear and seven angular measurements were taken on each radiograph. X and Y axes were established and coordinates locating each landmark were recorded on a Kontron Videoplan Image Analysis System. The changes in the horizontal and vertical dimensions following surgery were then assessed. No significant differences were found in the data relating to nasal and upper lip changes between those patients who had undergone additional mandibular surgery and those who had not. For the combined sample a significant correlation was found for the horizontal changes in the measurement between the upper lip (labrale superius) and upper incisal tip with a ratio o f 0.55 : 1. The patients were then divided according to whether or not a V-Y surgical closure of the vestibular incision had been performed and into those with thick or thin lips. The V-Y technique of closure of an incision enhances tissue flexibility by an interlocking of the flaps and improves lip aesthetics by increasing the amount of vermilion exposed. Ratios remained almost the same irrespective of the V-Y surgical procedure.Patients in the thin lip group had a mean soft tissue advancement at labrale superius of nearly three times more than those patients in the thick lip group.Incorporating a measure of lip tissue thickness into a multiple regression analysis improved the correlation in all areas studied. When a V-Y surgical closure procedure had been performed, inclusion of this variable in the regression equation marginally improved the correlation. As a result, suggestions were made to facilitate and to possibly enhance the accuracy o f preparing a visual treatment objective (VTO).